A numerical procedure for predicting the effects of distorted inflow conditions on the performance of axial flow fans - Thiart, G. D. (Stellenbosch : University of Stellenbosch, 2011)
Thesis (PhD (Mechanical Engineering))--University of Stellenbosch, 1990.